2020
DOI: 10.3390/jcm9113599
|View full text |Cite
|
Sign up to set email alerts
|

Biotherapies in Uveitis

Abstract: Non-infectious uveitis (NIU) represents one of the leading causes of blindness in developed countries. The therapeutic strategy aims to rapidly control intra-ocular inflammation, prevent irremediable ocular damage, allow corticosteroid sparing and save the vision, and has evolved over the last few years. Anterior NIU is mostly managed with topical treatment in adults. However, for intermediate, posterior and pan-uveitis, notably when both eyes are involved, systemic treatment is usually warranted. Biotherapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 128 publications
0
15
0
1
Order By: Relevance
“…When conventional immunosuppressive drugs are ineffective or have developed tolerance, biologics are the best choice for treatment, of which anti-TNF-α inhibitors are the most widely used ( Leclercq et al, 2020 ). Adalimumab has been approved by the FDA to treat patients with steroid-dependent or noninfectious uveitis with steroid contraindications ( Dick et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When conventional immunosuppressive drugs are ineffective or have developed tolerance, biologics are the best choice for treatment, of which anti-TNF-α inhibitors are the most widely used ( Leclercq et al, 2020 ). Adalimumab has been approved by the FDA to treat patients with steroid-dependent or noninfectious uveitis with steroid contraindications ( Dick et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab is recommended as the first-line treatment for Behçet’s disease-related uveitis ( Levy-Clarke et al, 2014 ). However, the failure rate of treatment with anti-TNF-α inhibitor drugs remains high, at approximately 30% ( Leclercq et al, 2020 ). Llorenc et al analyzed 392 noninfectious uveitis patients treated with adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment goals are the suppression of inflammation using steroids in combination with immunomodulators such as methotrexate, mycophenolate mofetil, and biologic modifiers in combination. 29 Key components of the inflammatory process in uveitis include the invasion of the eye by both T cells and macrophages, breakdown of the blood-retinal barrier, edema, and leakage of protein into the aqueous and vitreous. Prior work has shown that AP-Cav reduced the influx of inflammatory cells in an immune models of MS, asthma, and retinal disease [17][18][19]28 and reduced the actions and production of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Uveitis is an intraocular inflammation of different etiologies [1][2][3][4][5] characterized by leukocyte accumulation in ocular tissues and cytokine release. It is a painful condition and is associated with redness, photophobia, impaired vision, and blindness [6][7][8][9][10] Pharmacological treatment for uveitis includes corticosteroids, chemotherapeutic agents, and tumor necrosis factor (TNF)-α inhibitors [3,7,8,11], but the use of these drugs is limited by their serious side effects, such as increased ocular pressure or cytotoxicity [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is a painful condition and is associated with redness, photophobia, impaired vision, and blindness [6][7][8][9][10] Pharmacological treatment for uveitis includes corticosteroids, chemotherapeutic agents, and tumor necrosis factor (TNF)-α inhibitors [3,7,8,11], but the use of these drugs is limited by their serious side effects, such as increased ocular pressure or cytotoxicity [9,12]. However, recent advances in the mechanisms of inflammation and the discovery of several endogenous anti-inflammatory mediators have provided new therapeutic possibilities for uveitis treatment [5,7,10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%